Interconnecting controlled synthesis, plasmonic, and catalysis: from education to the next generation of nanomaterials for triggering green transformations - Silva, Anderson Gabriel Marques da (2017)
This dissertation is directed towards the fundamental understanding of the controlled synthesis of noble-metal (silver, gold, and palladium) and metal oxide (manganese and copper oxide) nanostructures as well as their applications in heterogeneous and plasmonic catalysis. In the first part of this work (Section 1), we provided a general background concerning the science of controlled nanomaterials, their syntheses, properties, and applications in catalysis and plasmonic catalysis. Then, we describe and developed a series of protocols for the synthesis of these nanomaterials with controlled sizes and structures (spheres, cubes, rods, shells, flowers, dendrites, and tadpoles), mainly focusing on the mechanistic understanding of their formation and how physical and chemical parameters (size, shape, composition, surface morphology) may influence/modify their catalytic properties (Sections 2 and 3). In Section 4, we turned our attention for the design of simple protocols for the synthesis of advanced nanomaterials that are interesting for green catalytic transformations applications. In this case, we envisioned the use of MnO2-Au nanomaterials (nanowires and nanoflowers) displaying several properties (unique pore structure, high surface area, ultrasmall Au NPs at the surface, high concentration of oxygen vacancies and Auδ+ species, strong metal-support interactions, and uniform shapes and sizes) that are desirable for catalyzing a series of green oxidation reactions in mild conditions (low temperatures and molecular oxygen or atmospheric air as the oxidants). In Section 5, we have demonstrated that catalysis and optical properties can be merged together to improve catalytic processes, the so called-plasmonic catalysis. This allowed us the use of visible light as the energy input to drive chemical transformations in mild conditions and then provide new insights regarding the various factors that affect SPR-mediated catalytic activities in plasmonic nanostructures. Finally, in Section 6, we focused our attention on how important is to introduce both nanoscience and the synthesis/characterization of nanomaterials having controlled physicochemical features to undergraduate students. Specifically, we have described simple laboratory experiments for the synthesis of nanomaterials (gold nanospheres and Cu(OH)2/CuO nanowires) displaying uniform sizes and shapes in order to investigate and explain their optical properties, catalytic activities and formation mechanisms.